Noncommunicable disease program for blood pressure ontrol in Tamil Nadu, India: Bridging care gaps among patients with hypertension in public health facilities - Kamaraj Pattabhi; Jerard Selvam; Azhagendran Sivalingam; Piyalee Pal; Savitha Kasivishwanathan; Suresh Arunachalam; T S Selvavinayagam; Prabhdeep Kaur (Wolters Kluwer Medknow Publications, 2022)
Background: Despite advances in hypertension care, developing countries have a high burden of uncontrolled blood pressure (BP). The Government of Tamil Nadu, India, initiated a noncommunicable disease program to improve hypertension management in public facilities. Method: We conducted cross-sectional surveys at baseline and follow-up to evaluate BP control after a multipronged intervention among patients with hypertension visiting public health facilities in Tamil Nadu. The intervention included protocol-based hypertension treatment, lifestyle counseling and monitoring by trained nurses, alongside monthly free drug refills. Descriptive statistics and adjusted odds ratio (AOR) for BP control were analyzed. Results: We surveyed 923 patients at baseline and 941 at follow-up. Most patients were over 60 years of age, with female predominance. Proportion of patients dispensed drugs for 30 days increased at follow-up (84.5%) compared to baseline (11.4%) (P < 0.01). Proportion of patients with BP control was 32.4% at baseline and 40.5% at follow-up (P < 0.001). AOR for BP control at follow-up was 1.4 (95% confidence interval 1.1-1.7, P < 0.05) after adjusting for age, sex, type of facility, and the number of drugs. Conclusion: Focussing on accessibility, availability, and affordability, the program facilitated the provision of free drugs and counseling, resulting in optimal BP control. Encouraging physician adherence to protocols and task sharing with nurses can help streamline sustainable hypertension management.